(5x-7)-2x=4(2x-3)+2

Simple and best practice solution for (5x-7)-2x=4(2x-3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-7)-2x=4(2x-3)+2 equation:



(5x-7)-2x=4(2x-3)+2
We move all terms to the left:
(5x-7)-2x-(4(2x-3)+2)=0
We add all the numbers together, and all the variables
-2x+(5x-7)-(4(2x-3)+2)=0
We get rid of parentheses
-2x+5x-(4(2x-3)+2)-7=0
We calculate terms in parentheses: -(4(2x-3)+2), so:
4(2x-3)+2
We multiply parentheses
8x-12+2
We add all the numbers together, and all the variables
8x-10
Back to the equation:
-(8x-10)
We add all the numbers together, and all the variables
3x-(8x-10)-7=0
We get rid of parentheses
3x-8x+10-7=0
We add all the numbers together, and all the variables
-5x+3=0
We move all terms containing x to the left, all other terms to the right
-5x=-3
x=-3/-5
x=3/5

See similar equations:

| P=350-r | | 12x-15=15x-3(8) | | (25x-2)=148 | | -7(-2y+4)-2y=6(y-4)-1 | | 3(3x+1)=5(x-4) | | 2×+55=3x+10 | | 8n+4n+2n-11n=9 | | 10x+15=5x+85 | | X+3+2x-1=60 | | 3x-2(x+10)=x-8 | | 7(w+5)=-4w+13 | | 2+5x-6=120 | | 15x-52=9x+2 | | 5/x=12.5/20 | | 2x2+26x+84=0 | | 10p-10p+5p=20 | | 7x-4(1+5x)=28-5x | | 64=^2x+3=2 | | 3(x+4)+2(2x−3)=27 | | -2x+6=10x+30 | | -8=60+b | | 7a-6a=11 | | 1x+2x-4-(-1x)=4 | | 3(x+12)=5x+36-2x | | 14z-6=14 | | X+3+2x-1+60+60+60=180 | | 3r-2r=18 | | 5(x+4)=5x-20 | | -5=-5(x+9) | | 4(x+3)2-11=89 | | 2(2m-5)-(6m+11)=33 | | b+13=-5b/3 |

Equations solver categories